"'Do This! Do That!' and Nothing Will Happen": Executive Orders and Bureaucratic Responsiveness. (January 2015) - Kennedy, Joshua B.
How effective is unilateral presidential power? Recent developments have shifted presidential scholarship in the direction of a more institutional approach, and one of the most important tenets of this work holds that the president has the ability to make policy on his own. However, there is significant anecdotal evidence suggesting that agency responsiveness to executive orders is not at all guaranteed. This study leverages a unique data set tracing the implementation of executive orders across 10 government agencies, and the results indicate that despite conventional wisdom, presidential directives are not universally implemented, and a host of factors come to bear on an agency's decision as to whether they will respond. This project represents among the first quantitative empirical assessments of the utility of unilateral power and suggests that the field may benefit most from shifting toward a bargaining-based model similar to those used in legislative scholarship.